ST elevation in lead aVR with malperfusion syndrome: sign of severe aortic dissection - Azlan Helmy Abd Samat,; Ida ZZ,; Yat, Keong Y; Isa MH, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Aortic dissection presenting with ST elevation in lead aVR of electrocardiogram is strongly associated with mortality. It is also associated with dissection involving the root of aorta and coronary vessels. We report a case of young male with hypertension, who presented with severe chest pain and unilateral lower limb pain. Physical examination of the left lower limb was consistent with acute limb ischemia. Electrocardiogram revealed acute anterolateral myocardial infarction together with ST elevation in aVR. Bedside transthoracic echocardiography showed a dilated aortic root measuring 4.51 cm with presence of intimal flap which raised the suspicion of dissection of root of aorta and left coronary artery. Computed tomography angiogram revealed aortic dissection from the root of aorta including the intimal flap near the origin of the left coronary artery, down to common iliac extending to the left iliac artery. Unfortunately, the patient opted for non-surgical intervention and succumbed 48 hours later. This case highlights that in case of aortic dissection, which presents with malperfusion syndrome, the presence of ST segment elevation at lead aVR should raise the suspicion for extensive aortic dissection involving the aortic root and left coronary artery which signifies unfavourable outcome.